A T7 exonuclease-RCA dual amplification system for high-sensitivity and high-selectivity analysis of microRNA. Issue 18 (17th April 2019) - Xu, Yan; Li, Yan; Zhou, Hongkun; Mei, Xiaoping; Ye, Jieyun; Chen, Wenyu; Kang, Yongli
Abstract : A novel combination of rolling circle amplification and T7 exonuclease-assisted amplification to achieve highly sensitive and selective detection of microRNA molecules was developed. Abstract : We developed a novel microRNA (miRNA) detection method with high-sensitivity and high-selectivity, based on rolling circle amplification (RCA) and the T7 exonuclease-assisted cyclic enzymatic amplification method. T4 DNA ligase is responsible for the selectivity, RCA enables the target miRNA to trigger DNA replication, and T7 Exo hydrolyzes the signal probe to further enhance the signal. This approach can detect miRNA with concentrations as low as 7 fM and can distinguish different miRNAs in the same family. In practical applications, this scheme can distinguish cancer cells by determining their let-7b miRNA content. This sensitive and selective detection scheme could therefore be used for early clinical diagnosis of cancers like those of the liver and lung.